Dampak Penggunaan Quick Response Code Indonesia Standard Bagi Kinerja UMKM Nasabah KUR PT. Pegadaian Cabang Wonosobo - Citraninggrat, Baiq Uswatunnisa; Siti Aisyah Hidayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the impact of using the Quick Response Code Indonesia Standard on the Performance of MSMEs that are customers of the KUR at PT. Pegadaian Wonosobo Branch. Utilizing a quantitative approach, this research collected data through survey using non-probability sampling techniques to obtain a representative sample of the population of MSME in Wonosobo and Banjarnegara Regency who use QRIS. The QRIS variable indicators include ease of use, understanding, satisfaction, and security, while the MSME performance indicators encompass profitability, number of customers, sales volume, and asset growth. Data analysis was conducted using SmartPLS 4 software to test the hypotheses and research model. The results indicate that the use of Quick Response Code Indonesia Standard has a positive and significant impact on improving MSME performance, with a coefficient value of 0.839, a t-statistic of 19.085 and p-value of 0.000. these findings suggest that the implementation of QRIS facilitates more efficient and secure transaction processes and contributes to increase profitability, customer number, sales and assets of MSMEs that are KUR customers.